x = ± 6istep-by-step explanation: x^2 = -36take the square root of each sidesqrt(x^2) = sqrt(-36)we know sqrt(ab) = sqrt(a) sqrt(b)x = ±sqrt(36) sqrt(-1)we know that sqrt (-1) = ix...Read More

1 more answers

investment b is an ordinary annuity with $3,909.64 in the account after one year. step-by-step explanation:...Read More

1 more answers

the standard deviation is around 0.6.i hope i ! if you need the unrounded version, just leave a comment down below....Read More

2 more answers

any options? step-by-step explanation:...Read More

1 more answers

(d)step-by-step explanation: given: the line in the graph passes through points (5,30) and (6,26).then, the equation of line is: [tex]y-y_{1}=\frac{y_{2}-y_{1}}{x_{2}-x_{1}}(x-x_{...Read More

2 more answers

- One bag contains 6 bags of apples if jeremy gave away five apples how...
- ∠1 and ∠2 are complementary. ∠1=x°∠2=(3x+30)° select from the drop d...
- Which system of linear equations has no solution? -5x + 2y = -8 - \fr...
- Will mark brainliest hurry the points represented by the table lie on...
- Solve the quadratic equation by completing the square. x^2-10x+15=0 fi...
- The pep squad sold c, cheeseburgers and h, hothogs at the friday night...
- Steven drives 78 miles on 3 gallons of gas find the miles per gallon...
- Acompany uses two vans to transport workers from a free parking lot to...
- If y=2×-3 determine the value of y when x=-15...
- The triangle shown is classified as...